Downside: The Perpetrator of Violence in the Representations of Social and Health Professionals - Procentese, Fortuna (Int J Environ Res Public Health, 2020)
Gender-based violence is a widespread phenomenon and pandemic that affects women’s lives. Many interventions have been activated for perpetrators, but the dropout rate is still high. In order to draw up guidelines for responsibly and sustainably dealing with the phenomenon, this study is aimed at investigating the professionals’ perception of the perpetrator as a useful element in designing innovative intervention policies. Open interviews were carried out with welfare and health professionals and the Grounded Theory Methodology was used to analyze the collected data. These results detect attitudes of social health personnel and their feelings of impotence towards gender-based perpetrators because of the emergence of an inevitable repetitiveness of the violent behavior, as well as the “normality of violence” in a patriarchal culture and its “transversality”. This reflective knowledge allows for the opportunity to develop best transformative attitudes toward the phenomenon. According to the results, it is urgent to establish an active and convinced alliance with the healthy part of the man, through specific prevention paths, in order to activate an authentic motivation for change and its sustainability.